The Cerebellum and SIDS: Disordered Breathing in a Mouse Model of Developmental Cerebellar Purkinje Cell Loss during Recovery from Hypercarbia - Calton, Michele A.; Howard, Jeremy R.; Harper, Ronald M.; Goldowitz, Dan; Mittleman, Guy (Frontiers in Neurology, 2016)
The cerebellum assists coordination of somatomotor, respiratory, and autonomic actions. Purkinje cell alterations or loss appear in Sudden Infant Death and Sudden Death in Epilepsy victims, possibly contributing to the fatal event. We evaluated breathing patterns in twelve wildtype and Lurcher mutant mice with 100% developmental cerebellar Purkinje cell loss under baseline (room air), and recovery from hypercapnia, a concern in sudden death events. Six mutant and six wildtype mice were exposed to four-minute blocks of increasing CO2 (2%, 4%, 6%, and 8%), separated by four-minute recovery intervals in room air. Breath-by-breath patterns, including depth of breathing and end-expiratory pause durations during recovery were recorded. No baseline genotypic differences emerged. However, during recovery, end-expiratory pause durations significantly lengthened in mutants, compared to wildtype mice, following the relatively low levels of CO2 exposure. Additionally, mutant mice exhibited signs of post-sigh disordered breathing during recovery following each exposure. Developmental cerebellar Purkinje cell loss significantly affects compensatory breathing patterns following mild CO2 exposure, possibly by inhibiting recovery from elevated CO2. These data implicate cerebellar Purkinje cells in the ability to recover from hypercarbia, suggesting that neuropathologic changes or loss of these cells contribute to inadequate ventilatory recovery to increased environmental CO2. Multiple disorders, including sudden infant death syndrome (SIDS), and sudden unexpected death in epilepsy (SUDEP) appear to involve both cardiorespiratory failure and loss or injury to cerebellar Purkinje cells; the findings support the concept that such neuropathology may precede and exert a prominent role in these fatal events.